Dave Robicheaux: The Glass Rainbow - Book 18 - Burke, James Lee, 1936- (New York : Simon & Schuster, 2010)
Beloved Burke hero Detective Dave Robicheaux returns to New Iberia, Louisiana, to solve a series of grisly murders. Seven young women in neighboring Jefferson Davis Parish have been brutally murdered. While the crimes have all the telltale signs of a serial killer, one death doesnt fit. Adding to Robicheauxs troubles is the matter of his daughter, Alafair, on leave from Stanford Law to put the finishing touches on her novel. Her literary pursuit has led her into the arms of Kermit Abelard. But Robicheaux begins to fear that Alafair might be destroyed by the man she loves.
Keywords: Robicheaux, Dave (Fictitious character) -- Fiction; Police -- Louisiana; New Iberia; Fiction; New Iberia (La.) -- Fiction; Fiction